Efficacy and clinical outcomes of proximal splenic artery embolization in patients with chemotherapy induced thrombocytopenia - Daniel Körfer; Madelon Dijkstra; Brian Schiro; Constantino Pena; Gina Landinez; Govindarajan Narayanan; Alex Powell; Ripal Gandhi (Langenbeck's Archives of Surgery, 2026)
Abstract Purpose This retrospective study aims to investigate efficacy and clinical outcomes of proximal splenic artery embolization (PSAE) in patients with chemotherapy induced thrombocytopenia (CIT). Methods PSAE was performed in thirteen patients with CIT (6:7, M:F; median age: 55y; range: 39-76y) with underlying malignancy (colorectal carcinoma: n = 6; pancreatic carcinoma: n = 3; other: n = 4). Median platelet counts were calculated prior to chemotherapy, at nadir resulting in chemotherapy discontinuation, prior to SAE, immediately and at the maximum following SAE. Additionally, the time until re-initiation of chemotherapy was calculated. Results Technical success was 100%, with no adverse events or 30-day mortality. Vascular plugs ( n = 9) and coils ( n = 11) were the most frequently used devices. Median platelet count pre-chemotherapy was 201 × 10(9)/L (range: 100–423 × 10(9)/L), platelet count nadir was 45 × 10(9)/L (range: 21–69 × 10(9)/L), and pre-SAE platelet count was 82 × 10(9)/L (range: 45–171 × 10(9)/L). After proximal SAE, median platelet count increased significantly (110 × 10(9)/L; range: 68–169 × 10(9)/L) compared to pre-procedure platelet count ( p = 0.027). Median platelet count at the maximum at follow-up was 191 × 10(9)/L (range: 31–518 × 10(9)/L). Chemotherapy was re-initiated after a median of 15 days (range: 7-50d). Conclusion Proximal SAE is a safe and effective treatment option in patients with CIT, with potential benefits in early re-initiation of chemotherapy. Further studies should be conducted to evaluate the longer-term effects of the procedure, further identify eligible patients, and compare to distal SAE.